Does the level of cash always increase with firm size? Theory and evidence from small firms - Kakhbod, Ali; Reppen, A Max; Umar, Tarik; Xing, Hao (Review of Finance, 2025)
Large firms typically increase their cash holdings as they grow to buffer against greater cash flow volatility. However, data on 11.2 million small firms show the opposite: cash levels decline as firms expand. We explain this phenomenon through a liquidity management model. Small firms with limited cash flows rely on cash reserves for investment due to costly external financing. As they grow, they do not fully replenish their cash reserves because investment incentives decrease, and increased cash flows support more of their anticipated investments. This mechanism generates a negative correlation between cash holdings and firm size among small firms.